A Review on the phytochemical characterization of Araucaria columnaris (International Journal of Food and Nutritional Sciences, 2023)
This review focused on studies concentrated on identifying phytochemicals in Araucariacolumnaris. This species is popular as an ornamental plant and its pharmacological activitiesand therapeutic uses are not commonly known. We screened various bibliographic databasesand retrieved 13 relevant studies, which explored Araucaria columnaris chemical constitution.